Engagement in science, engineering and technology in the early years: A cultural-historical reading - SUE MARCH; MARILYN FLEER (Metaichmio Publications, 2009)
This paper seeks answers to the question "what engages young children in science, engineering and technology (SET)?". A review of the SET literature is undertaken to find out what are the dominant themes noted in the research literature for engaging young children in SET. Two kinds of analyses are presented in this paper. The first analysis draws upon developmental theory because it is still the dominant worldview within early childhood education, and is closely aligned with constructivism, the major theory within SET education research. This analysis gives some insights into the concept of engagement from a developmental perspective. However, many of the findings identified in the studies reviewed could not easily fit within a traditional developmental framework. A second analysis was undertaken, using cultural-historical theory. It was found that engagement could be explained more fully when it was theorised in relation to Vygotsky's (1987) and Leont'ev's (1978) concept of "motives" in the context of Kravtsova's (2008) concept of the "zone of potential development". This latter theorisation allowed for a richer discussion of SET engagement for early childhood education. The paper concludes with a model of SET engagement for early childhood education.